2005
DOI: 10.1021/jf048394r
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Immunoassays for the Determination of Peanut and Hazelnut Traces in Foods

Abstract: People suffering from food allergies are dependent on accurate food labeling, as an avoidance diet is the only effective countermeasure. Even a small amount of allergenic protein can trigger severe reactions in highly sensitized patients. Therefore, sensitive and reliable tests are needed to detect potential cross-contamination. In this paper two fast sandwich immunoassays are described for the determination of peanut (Arachis hypogaea) and hazelnut (Corylus avellana) traces in complex food matrices. Mouse mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Some researchers have developed successfully ELISA techniques (using polyclonal antibodies and MAbs) to detect them into ice creams, chocolates or sauces (Kiening et al, 2005;Yeung & Collins, 1996).…”
Section: Allergen Ingredientsmentioning
confidence: 99%
“…Some researchers have developed successfully ELISA techniques (using polyclonal antibodies and MAbs) to detect them into ice creams, chocolates or sauces (Kiening et al, 2005;Yeung & Collins, 1996).…”
Section: Allergen Ingredientsmentioning
confidence: 99%
“…At present, different techniques, such as immunoassays, immunoblotting, immuno-electrophoresis, real-time polymerase chain reaction (PCR), PCR-enzyme-linked immunosorbent assay (ELISA) and mass-spectrometry are available to detect and/or quantify (trace amounts of) hazelnut proteins (Kiening et al 2005, Ben Rejeb et al 2003, Arlorio et al 2007, Hird et al 2000, van Hengel 2007, Blais and Phillippe 2001, Yman et al 2006, Scheibe et al 2001, Holzhauser et al 2002. However, the value of the results obtained with these techniques will strongly depend on the quality of the extract used.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of antibody reactivity of six commercial ELISA kits against purified peafi nut allergens (Ara h 1, Ara h 2, Ara h 3, and Ara h 6) demonstrated that five commercial kits were most sensitive in detecting Ara h 3 followed fi by Ara h 1, whereas one kit showed greater sensitivity in the detection of Ara h 2 and Ara h 6 [77]. [86][87][88], macadamia nut [89], pecan [90], pistachio [91], and walnut [92,93]. As with peanut, the associated allergenicity and abundance of seed storage proteins in tree nuts make them candidate proteins for the detection of tree nuts in foods.…”
Section: Peanutmentioning
confidence: 99%